1984
DOI: 10.1148/radiology.152.3.6463251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT and MR in 400 patients with suspected disease of the brain and cervical spinal cord.

Abstract: Magnetic resonance imaging (MR) (0.35 T) and computed tomography (CT) were compared in 400 consecutive patients with suspected disease of the brain and cervical spinal cord. Of 325 positive diagnoses, MR detected abnormality while CT was normal in 93; MR was more specific in 68; MR and CT gave equivalent information in 129; CT was more specific in 32; and CT was positive while MR was normal in 3. MR was superior to CT in detection of multiple sclerosis, subcortical arteriosclerotic encephalopathy, posterior fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(56 citation statements)
references
References 0 publications
0
54
0
2
Order By: Relevance
“…In a recent comparison of MR and CT in 400 consecutive cases of suspected disease in the brain and cervical cord, MR was shown to be more sensitive than CT in 30% of the cases referred to a large community hospital over a five-month period. 3 For this reason, MR is rapidly being implemented at university medical centers, large community hospitals, and at freestanding clinics. In view of the expected widespread use of these devices in the near future, it is incumbent upon the referring physician to be conversant with the basic principles of magnetic resonance imaging and to be familiar with the current clinical indications for MR, particularly in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent comparison of MR and CT in 400 consecutive cases of suspected disease in the brain and cervical cord, MR was shown to be more sensitive than CT in 30% of the cases referred to a large community hospital over a five-month period. 3 For this reason, MR is rapidly being implemented at university medical centers, large community hospitals, and at freestanding clinics. In view of the expected widespread use of these devices in the near future, it is incumbent upon the referring physician to be conversant with the basic principles of magnetic resonance imaging and to be familiar with the current clinical indications for MR, particularly in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…At present, CT scan with contrast is also superior to magnetic resonance imaging in detecting single or multiple meningiomas. 34 In all reported cases, the histology of multiple meningiomas was not different from that in benign single meningioma. Due to this fact, and because these tumors often reach large sizes before they are discovered and become difficult to remove, a high index of suspicion for the possible presence of more than one meningioma is warranted in the clinical and radiologic investigation of these patients.…”
Section: Discussionmentioning
confidence: 81%
“…For example, Fiirgaard et al suggested that MRI is superior in estimating the volume of acoustic neuroma than CT scan and with less inter-examiner difference [104]. MRI was reported to be better in identifying suspected disease of the brain and cervical spinal cord [105]. The sensitivity for detecting bony osteolytic lesions was 51.7% for radiography, 74.7% for computed tomography, and 95.4% for magnetic resonance imaging as reported by Walde et al [106].…”
Section: Discussionmentioning
confidence: 96%